Metabolic Engineering of Escherichia coli for Efficient Production of Benzyl Alcohol - Xue, Bingqing; Lu, Liangyu; Hu, Chenyu; Cheng, Yiyuan; Wang, Xiaolei; Zhang, Wen; Wang, Tong; Ren, Junda; Shen, Xiaolin; Sun, Xinxiao; Wang, Jia; Yuan, Qipeng (Journal of agricultural and food chemistry, 2025)
Benzyl alcohol (BALC) is a naturally occurring compound widely used in the fragrance, pharmaceutical, and chemical industries. Traditional chemical synthesis involves toxic materials and costly purification, and the resulting products are often labeled as "artificial fragrances", which are generally less favored by consumers due to concerns about their safety, sustainability, and environmental impact. Biosynthesis offers a sustainable alternative for "naturally derived" BALC, but existing pathways face insufficient precursors and bottleneck enzyme, limiting titers to 114 mg/L. To address these challenges, we employed systematic metabolic engineering strategies, including the deletion of competing pathways, enhancement of the shikimate pathway, and alleviation of feedback inhibition, to redirect carbon flux into the BALC biosynthetic pathway. Furthermore, the rate-limiting step was addressed by screening for efficient candidate enzymes and optimizing their expression. As a result, a titer of 10.26 g/L BALC was achieved under fed-batch conditions in a 3 L fermenter, representing a 90-fold increase compared with previously reported strains. This study lays a foundation for the large-scale industrial biosynthesis of BALC.